Productivity in religious orders: a management by values applied approach. - Jurado-Caraballo, María Ángeles; Rodríguez-Fernández, María Mercedes (Elsevier, 2021)
Purpose: In this theoretical-empirical study, we analyse work methodologies of Spanish Religious Orders, and their relationship with productivity, efficacy and efficiency. Design/methodology/approach: In the literature review we have compiled all the applicable theories. Amongst them, Management by Values stands out and has served as the framework for the hypotheses. To test the latter, we have obtained data from face-to-face surveys, obtaining 112 valid answers. Ordinary Least Squares and Logit Model have been proposed. Findings: A greater compromise of the individual with the organization generated greater values of productivity, and its higher value in the case of the female Orders when compared to the male Orders. Research limitations: The conclusions presented here only refer to the data of religious organizations of M alaga (Spain) that have been analysed. Future research should consider the changes brought about by the possible merger of the different Orders and the analysis of the social work of the Church through its non-profit organizations (C aritas or Manos Unidas). Practical implications: This study can be translatable to profit-seeking organizations. If work methodology and coordinating tasks are appropriate for religious organizations, then they should also be beneficial for-profit companies. Originality/value: Management by Values occupies an essential place in the direction and coordination of daily tasks and the life of religious communities. Their levels of productivity, efficacy and efficiency are a result of the strong link that joins the members to the aim of the organization.
Keywords: Órdenes y congregaciones religiosas - Gestión; Valores (Filosofía) - Trabajo; Management by values; Productivity; Work organization; Religious organizations